A Contribution Toward a Research Agenda: Identifying Impact Factors of Mass Customization on Environmental Sustainability - Pourabdollahian, Golboo; Steiner, Frank; Rasmussen, Ole Horn; Hankammer, Stephan (International Journal of Industrial Engineering and Management, 2014)
Mass customization (MC) has been broadly discussed as a potential business model for heterogeneous marketsin the management literature. In market settings that are characterized by high levels of customer need heterogeneity, MC has to be considered as an economically viable strategy. However, it might not be sufficient to assess business models solely on the basis of economic indicators. Environmental problems and the exacerbating climate change have sparked a global debate about ecological thinking and sustainability. In this context, existing literature describes the need for strategies that are sustainable in terms of economic, social and environmental aspects. In accordance with this aspect, more and more authors claim that MC –besides being an economically attractive business approach –also carries the potential to be an environmentally and socially beneficial business model. This paper aims to identify potential impact factors of MC on sustainability in order to establish a research agenda concerning the role of MC for sustainability. Article history: Received (17.07.2014); Revised (19.11.2014); Accepted (14.12.2014)